Screening of Novel Pharmacogenetic Candidates for Mercaptopurine-Induced Toxicity in Patients With Acute Lymphoblastic Leukemia - Cao, Minyuan; Yin, Dandan; Qin, Yun; Liao, Fei; Su, Yali; Xia, Xuyang; Gao, Ju; Zhu, Yiping; Zhang, Wei; Shu, Yang; Lu, Xiaoxi (Frontiers in Pharmacology, 2020)
A small proportion of patients with acute lymphoblastic leukemia may experience severe leukopenia after treating with 6-mercaptopurine (6MP), which can be largely explained by germline variants in TPMT and NUDT15. However, a minority of patients suffered such adverse drug reaction have NUDT15wt/wtTPMTwt/wt genotype, indicating other genetic factors may take part in. In this study, we genotyped 539 exon-located non-silent pharmacogenetic variants in genes involved phase I/II of drug metabolism in 173 pediatric patients with acute lymphoblastic leukemia, and conducted association screening for 6MP-induced leucopenia. Besides NUDT15 (rs116855232, P = 6.4 × 10-11) and TPMT (rs1142345, P = 0.003), several novel variants were identified with the top signal located in CYP2A7 gene (i.e., rs73032311, P = 0.0007), which is independent of NUDT15/TPMT variant. In addition, a variant (i.e., rs4680) in COMT is significantly associated with 6-MP induced hepatoxicity (P = 0.007). In conclusion, variants in CYP2A7 and COMT may be considered as novel potential pharmacogenetic markers for 6MP-induced toxicities, but additional independent validation with large sample size and investigation of related mechanisms are further needed.